Income inequality and their impacts on the Brazilian household carbon footprint - Tudeschini, Luís Gustavo (2018)
The dissertation explores the link between two crucial development challenges for the Brazilian society: income inequality and climate change. In a developing country like Brazil, there is still a large room for income growth and distributional improvements. The design of social and distributional policies need to understand the links between income level, consumer behavior, and greenhouse gases (GHG) emissions. Two main objectives are set to tackle these links. First, to analyze the unequal contribution of household consumption across income groups on the Brazilian GHG emissions, and second, to understand the impacts of changes in income distribution on the total Brazilian household GHG footprint. The development of these objectives brings two main innovative contributions: a price index method that corrects the distortion on emission allocation caused those price variation, and detailed analysis on the contribution of the consumption items to the household carbon footprint. Additionally, four questions derive from these objectives: i) how do the consumption patterns of households in different income groups affect their GHG footprints?, ii) what is the impact of prices variations across income classes on GHG footprint estimations?, iii) what is the emission cost of building a more egalitarian Brazilian society?, and iv) how the improvement or worsening of the income distribution would affect the relative importance of the consumption sectors on the household emissions?. To answer the first question, an Environmentally Extended Multiregional Input-Output model (EE-MRIO) was combined with the consumption data from the household budget survey. The second question was tackled by estimating the price variations across the income classes. To answer the third and fourth questions, five scenarios were developed to estimate the impact of inequality changes on the household consumption and carbon footprint. These scenarios were built based on the Shared Socioeconomic Pathways (SSPs) and the Kaya Identity. The primary results show that, on the one hand, increasing the families income to a level just above the poverty threshold has a relatively low emission cost. On the other hand, the ascension of households to the upper-income group (G10) induces a significant impact on the total consumption and related emission, since the emission per capita of this group (10 tCO2e) 11 is almost five times higher than the national average. Secondly, the most egalitarian scenario would emit about 12% more GHG than the least egalitarian one. Previous studies have shown that technological and consumption shifts have the potential to mitigate these increments on the emission. Thus, given the social and economic benefits of improving the distribution, this increment would be a fair price to pay.